Penerapan Projek Penguatan Profil Pelajar Pancasila Dengan Tema Kewirausahaan Pada SMA Negeri 2 Tarakan - Rahmi Nur Islami; Nurjannatul Hasanah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The project to strengthen the Pancasila or P5 student profile is one part of the Merdeka curriculum implemented in schools. SMA Negeri 2 Tarakan implements P5 by taking the theme of entrepreneurship. Entrepreneurship is the process of identifying, developing, and bringing a vision to run something in life. Activity P5 aims to determine and analyze the effectiveness of the Pancasila Student Profile Strengthening Project in fostering students' entrepreneurial spirit.